Evaluation of phosphorus uptake and use efficiency and nitrogen fixation potential by African clovers - Mugwira, L.M.; Haque, I.; Lupwayi, N.Z.; Luyindula, N. (Elsevier, 1997)
Phosphorus deficiency is the major soil fertility problem limiting forage production in many parts of Africa. The objective of this study was to screen African Trifolium species for dry matter production, nutrient use efficiency and nitrogen fixation potential at different rates of applied Twenty accessions of native Ethiopian clovers were grown in a greenhouse on Vertisol at P rates of 0, 12.5, 25, 37.5 and 60 mg P kg-1 soil. The experiment was conducted in Addis Ababa, Ethiopia. In the absence of P fertilizer, there was total inhibition of nodulation in all the accessions, which virtually eliminated the potential for the clovers to fix nitorgen. Nodulation, shoot and root dry matter (DM) increased with added Shoot DM yields at 50 mg P kg-1 soil were 15-to 70-fold higher than those without applied Corresponding responses in root DM were 10- to 48-fold. Trifolium decorum accessions ILRI9682 and ILRI6264 had the highest shoot and root DM, N and P uptake, and N efficiency ratio, but the highest P efficiency ratios were found in Trifolium steunderi accession ILRI9720.